Design of temperature controk system for baby incubator transport using PID FUZZY Method - Sipul, Elshaday (Jurnal Teknokes, 2025)
Baby incubator transport is designed to keep the baby's body temperature in a stable condition while traveling, especially for babies who are born prematurely or have medical conditions that require proper temperature control. However, temperature fluctuations in baby incubator transport are often a problem that can affect the safety of the baby. to overcome this, the research proposes the design of a temperature control system on baby incubator transport using a combination of PID (Proportional-Integral-Derivative) and Fuzzy Logic methods. The PID method is used for precession temperature control, while Fuzzy Logic serves to dynamically adjust PID parameters to overcome non-linearity and system uncertainty. The test results show that the PID-fuzzy based temperature control system is able to maintain temperature stability with fast response and low overshot rate compared to conventional methods